Antioxidant, Discoloration, Reducing Sugar, Free Amino Acids Profiling Of Black Garlic Processed On Electric Rice-Cooker - Nur, Alfi; Supriyadi, Supriyadi; Santoso, Umar (Department of Technology of Agricultural product (THP) Jambi University, 2024)
Black garlic is garlic processed by heating at a controlled temperature and humidity. The heating process of black garlic is garlic processed by heating at controlled temperature and humidity. Black garlic can be prepared in an electric rice cooker, but information is limited. The purpose of this study was to determine the color, pH, water content, antioxidant activity, flavonoids, phenolics, reducing sugar, and free amino acids of black garlic that were processed in an electric rice cooker during the heating time. The production of black garlic in this study uses an electric rice cooker. As for heating black garlic with an electric rice cooker using a temperature of 71-74 0C, RH 44-48%, and for 24 days. Heating time used for black garlic production was 0, 6, 12, 18, and 24 days. This study used a randomized block design. Black garlic cooked in an electric rice cooker during the heating time showed a darker color change towards browning and decreased water content and pH. Antioxidant activity, total flavonoids, phenolics, reducing sugar and free amino acids black garlic increased and 24 days heating time had the highest antioxidant potential. The Maillard reaction of black garlic has a higher antioxidant potential and darker discoloration than garlic.